2016
DOI: 10.2224/sbp.2016.44.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Temperament Trait of Sensory Processing Sensitivity and Emotional Reactivity

Abstract: S S S t t t o o o n n n y y y B B B r r r o o o o o o k k k U U U n n n i i i v v v e e e r r r s s s i i i t t t y y yThe official electronic file of this thesis or dissertation is maintained by the University Libraries on behalf of The Graduate School at Stony Brook University. ii © © © A A A l l l l l l R R R i i i g g g h h h t t t s s s R R R e e e s Stony Brook UniversityThe Graduate School Jadwiga Anna JagiellowiczWe, the dissertation committee for the above candidate for the Doctor of Philosophy degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 73 publications
4
45
0
5
Order By: Relevance
“…These findings are consistent with research showing that emotional bonds between actors and perceivers facilitate mutual intention perception, and those with stronger bonds show greater intention understanding (e.g., Ortigue and Bianchi-Demicheli 2008). Our results were also in-line with previous SPS studies showing strong responses to positive stimuli (Jagiellowicz 2012). It is interesting to note that in our study we found no evidence of activation in the amygdala -a brain region that is known to be involved in emotional processing-as a function of SPS in response to emotional social stimuli.…”
Section: Brain Regionsupporting
confidence: 93%
“…These findings are consistent with research showing that emotional bonds between actors and perceivers facilitate mutual intention perception, and those with stronger bonds show greater intention understanding (e.g., Ortigue and Bianchi-Demicheli 2008). Our results were also in-line with previous SPS studies showing strong responses to positive stimuli (Jagiellowicz 2012). It is interesting to note that in our study we found no evidence of activation in the amygdala -a brain region that is known to be involved in emotional processing-as a function of SPS in response to emotional social stimuli.…”
Section: Brain Regionsupporting
confidence: 93%
“…This result would be expected given that the emotional importance of a subject tends to determine how thoroughly it is processed (Baumeister, Vohs, DeWall, & Zhang, ). In a series of behavioral and fMRI experiments (Acevedo et al, ; Jagiellowicz, Aron, & Aron, ), high‐SPS individuals responded more strongly to both standard pleasant (e.g., puppies, birthday cakes) and unpleasant (e.g., snakes, spiders) photos compared with neutral ones, with the response to pleasant photos being particularly strong. This greater responsiveness may well influence all the PSE factors and make one more susceptible to parenting experiences, in that high‐SPS individuals would find the negative parts of parenting more negative and the positive parts more positive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thereby, they do refer to any, high as well as low‐SPS, expatriate. However, because HSPs are aware of and more reactive to both positive and negative stimuli to a higher degree (Jagiellowicz et al ., ), they are by their nature more prone to be overwhelmed (Aron, ). Thus, high‐SPS expatriates are expected to be stressed more frequently in the new environment abroad.…”
Section: Towards a Research Model Of Expatriates' Sensory Processingmentioning
confidence: 99%